Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing Pada Materi Fungi Kelas X SMA : The Development Of Student Worksheets Based On Guided Inquiry On Fungi Material In Class X Of Senior High School - Estitika Estitika; Haryanto Haryanto; Pinta Murni (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to develop LKPD based on Guided Inquiry for Class X Fungi Materials in SMA. The development model used in this research is the Plomp development model which consists of three stages, namely; (1) initial investigation, (2) development and manufacture of prototypes, and (3) assessment. The LKPD was tested on tenth-grade students of SMA IT Diniyyah Al-Azhar Jambi City and biology subject teachers. The results of the design expert's assessment, it was found that the LKPD design was very feasible, with a score of 61 or 95.31%. Meanwhile, from the results of the material expert assessment, it was found that the material on the LKPD was very feasible, with a score of 110 or 86%. The results of individual trials, small group trials, and large-group trials, it was found that LKPD has a very practical level of practicality, with the acquisition of practicality scores of 34.67, 36.40 and 34.60, respectively. Likewise, the results of the practicality assessment by the teacher showed that the LKPD had a very practical level of practicality, with a practicality score of 35. It was concluded that the LKPD based on Guided Inquiry on Fungic Materials was very feasible and practical to use in learning activities. Keywords: Development, LKPD, Guided Inquiry, Fungi Material Â Abstrak. Penelitian ini bertujuan mengembangkan LKPD berbasis Inkuiri Terbimbing Materi Fungi Kelas X SMA. Model pengembangan yang digunakan adalah model pengembangan Plomp yang terdiri dari tiga tahapan, yaitu; (1) investigasi awal, (2) pengembangan dan pembuatan prototype, dan (3) penilaian. LKPD diujicobakan kepada siswa kelas X SMA IT Diniyyah Al-Azhar Kota Jambi dan guru mata pelajaran biologi. Hasil penilaian ahli desain, didapatkan bahwa desain LKPD sudah sangat layak, dengan perolehan skor sebesar 61 atau 95,31%. Sementara dari hasil penilaian ahli materi, didapatkan bahwa materi pada LKPD sudah sangat layak, dengan perolehan skor sebesar 110 atau 86%. Hasil ujicoba perorangan, uji coba kelompok kecil, dan ujicoba kelompok besar, didapatkan bahwa LKPD memiliki tingkat kepraktisan sangat praktis, dengan perolehan skor praktikalitas masing-masing sebesar 34,67, 36,40 dan 34,60. Begitupula hasil penilaian praktikalitas oleh guru didapatkan bahwa LKPD memiliki tingkat kepraktisan sangat praktis, dengan perolehan skor praktikalitas sebesar 35. Disimpulkan bahwa LKPD berbasis Inkuiri Terbimbing Materi Fungi sudah sangat layak dan praktis untuk digunakan dalam kegiatan pembelajaran. Kata kunci: Pengembangan, LKPD, Inkuiri Terbimbing, Materi Fungi